Administrators’ perceptions of the effectiveness of alternatively certified agricultural educators in Kansas - Kuhlmann, Arika (Haresnape) (Kansas State University, 2019)
As the number of alternatively certified educators rises, the effectiveness of these teachers is under investigation. The purpose of this study was to determine the effectiveness of alternatively certified agricultural educators in Kansas as perceived by their administrators. Survey research was used to identify areas of least effectiveness of the alternatively certified agricultural educators under evaluation. The survey was divided into seven construct areas with a total of 35 competencies being evaluated among the constructs. The construct areas under evaluation were; (1) subject area knowledge, (2) classroom management and discipline, (3) instructional planning process and teaching methods, (4) community relationship, (5) professional development, (6) management of the FFA chapter, and (7) management of Supervised Agricultural Experiences. The population consisted of 36 administrators of alternatively certified agricultural educators in Kansas teaching during the 2018-2019 school year. The survey allowed the administrators to identify their perceived level of effectiveness of the alternatively certified agricultural educator under their supervision using a 5-point Likert scale. The survey results indicated that the alternatively certified agricultural educators in Kansas are least effective at managing Supervised Agricultural Experiences (SAEs) and need to improve at requiring all students in the agriculture program to have a SAE, encouraging FFA members to complete award applications for their SAE, and analyzing and reflecting on student data to guide planning, instruction, and student growth. The survey results also showed the alternatively certified teachers are ineffective at conducting SAE visits for each student to learn about their experiences. Alternatively certified agricultural educators in Kansas should take time to attend professional development opportunities focused on Supervised Agricultural Experiences which will allow them to become more effective in that area of their agriculture program.
Keywords: Alternative certification; Agricultural education; Effectiveness; Transition to teaching